SOSIALISASI PELAKSANAAN PEMILIHAN UMUM TAHUN 2024 WARGA RT 04 RW 16 KABUPATEN BEKASI - Ana Chaerunisyah; Noviandari Sari Utami; Endang Susanti; Muhammad Sholeh; Ranti Noviyanti (Gapenas Publisher, 2023)
General elections serve as a democratic means to realize a government system based on the sovereignty of the people. However, many community members still lack understanding of the procedures involved in general elections. Therefore, it is necessary to conduct socialization on the implementation of general elections for the public. The purpose of this socialization is to raise awareness among the community about the importance of general elections and provide information on the procedures involved. The socialization was carried out for residents of RT 04 RW 16, Bekasi District, on December 17, 2023, using an engaging secondary socialization approach. During this socialization, various topics were covered, including the significance of the community's role in the 2024 general elections and the prevention of abstention (GOLPUT) activities. The results of the socialization indicate that residents of RT 04 RW 16 have gained a better understanding of the procedures involved in general elections. They are also more motivated to exercise their voting rights in the 2024 general elections